2013
DOI: 10.1007/s13165-013-0041-3
|View full text |Cite
|
Sign up to set email alerts
|

Health and welfare of organic pigs in Europe assessed with animal-based parameters

Abstract: Organic pig farming aims at maintaining a high health and welfare state of the animals through appropriate housing, management and feeding. Better knowledge of health and welfare indicators should help to identify critical points and hence to improve health and welfare as well as performance of organic pigs. This paper describes the health and welfare of organic pigs from 101 farms across six EU countries, using selected animal-based parameters from the Welfare Quality® protocol. Parameters were collected in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Five piglets fed the control diet, four piglets fed diet R 20.2, six piglets fed diet T 20.2 and two piglets fed diet T 30.2 were treated, which corresponds to 14, 11, 16 and 5% of the piglets, respectively. A recent study on health and welfare of organic pigs in six European countries found a highly variable prevalence of diarrhea with values between 0 and 100%, but the median prevalence was 0% because groups were scored rather than piglets (Dippel et al, 2013). Weekly gait scoring in experiment 1 and at the end of each replicate in experiment 2 did not reveal any signs of lameness which might have indicated nerve disorders caused by ODAP.…”
Section: Resultsmentioning
confidence: 99%
“…Five piglets fed the control diet, four piglets fed diet R 20.2, six piglets fed diet T 20.2 and two piglets fed diet T 30.2 were treated, which corresponds to 14, 11, 16 and 5% of the piglets, respectively. A recent study on health and welfare of organic pigs in six European countries found a highly variable prevalence of diarrhea with values between 0 and 100%, but the median prevalence was 0% because groups were scored rather than piglets (Dippel et al, 2013). Weekly gait scoring in experiment 1 and at the end of each replicate in experiment 2 did not reveal any signs of lameness which might have indicated nerve disorders caused by ODAP.…”
Section: Resultsmentioning
confidence: 99%
“…In total, antibiotic treatment was necessary for 13 piglets fed the control diet, 10 piglets fed diet H 10, 12 piglets fed diet D 10 and 13 piglets fed diet D 16, which corresponds to 37, 29, 34 and 37% of the piglets, respectively. In a comprehensive study examining health and welfare of organic pigs in six European countries, the prevalence of diarrhea was found to be highly variable with values between 0 and 100%, but the median prevalence was 0% because groups were scored rather than piglets 41 . A study on 106 conventional French pig farms using medicated creep feed and weaning piglets at 27 days revealed a maximum prevalence of 35% pens affected by diarrhea around 7–9 days post-weaning, which is in accordance to the observations made in the present study 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Lameness/leg/foot health Lameness of sows was less prevalent in organic compared to conventional herds (Dippel et al 2014;Knage-Rasmussen et al 2014) and less prevalent in all-yearround and partly outdoor sow housing systems compared to indoor systems (Leeb et al 2019). However, according to Früh et al (2014), all European countries involved in the study (Denmark, Germany, Italy, Sweden, Switzerland and the UK), reported leg problems (i.e.…”
Section: Respiratory Diseasesmentioning
confidence: 99%
“…Metabolic/digestive disorders Thinness or poor body condition of organic sows is a main concern in several European countries (Simoneit et al 2012;Dippel et al 2014;Früh et al 2014). Weissensteiner et al (2018) found that sows with larger litters had lower feed intake and greater weight loss during 1-2 weeks postpartum, when fed diets with high proportion of home-grown ingredients with low protein content.…”
Section: Pig Productionmentioning
confidence: 99%
See 1 more Smart Citation